Knowledge, perception and practice of infection control among Ministry of Health staff during COVID-19 outbreak in Malaysia - Halizah Mat Rifin; Shubash Shander Ganapathy; Wan Shakira Rodzlan Hasani; Komathi Perialathan; Manimaran Krishnan Kaundan; Noor Ani Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Coronavirus Disease 2019 (COVID-19) was declared as a pandemic in the middle of March as the disease is highly contagious and spread very quickly throughout the world. Understanding the knowledge and practice among healthcare staffs is also crucial especially among the frontlines staffs as they need to be able to protect themselves, and facilitate in educating their patients and public regarding disease prevention measures. The objective of this study is to assess knowledge, practice and perception on the effectiveness of the preventive measures taken by Ministry of Health (MOH) staffs to prevent transmission of the disease and measures they would take should they develop symptoms of the disease on COVID-19 disease. Methodology: We conducted a cross-sectional online survey from 30th March 2020 to 6th April 2020 among the Ministry of health staffs. 1719 staffs completed the survey. Results: The overall correct rate of knowledge was 46.6%. Most participants held good perceptions (range from 77.8% to 98.4%) and good practices (range from 88.8% to 99.7%) towards COVID-19 preventive measure. Meanwhile, the preventive measures practices if they develop symptoms of COVID-19 range from 89.8% to 99.7% and for the perception, it ranges from 85.5% to 98.9%. Conclusion: There are also still some lower components perceptions and practices than expected. Additional education intervention and campaigns are required to provide the Ministry of health staffs with adequate knowledge towards COVID-19 clinical presentation, general knowledge and transmission route of COVID-19, and to increase the perception and practice on some perceptions and practices of the preventive measures.